Estudio de las alternativas económicas para el Plan de Desarrollo Territorial del GAD Parroquial de Canuto - Alcívar Zambrano, Evelyn Nicolle (2024)
The objective of this research was to analyze the economic alternatives in Canuto parish for incorporation into the Parish Territorial Development Plan. The methodology used included inductive, deductive, and analytical-synthetic methods, as well as bibliographic and field research. Interviews and surveys were also employed as data collection techniques. The results indicate that the economic development policies implemented by the Parish GAD in Canuto are designed based on the various programs and projects this entity has planned according to the economic component of the current PDOT. Actions such as support for the agro-productive sector, land legalization, training in micro-entrepreneurship, and productive initiatives aim to promote the productive growth of the locality. Furthermore, the identification of implemented economic alternatives shows that most of the population is engaged in activities such as agriculture and livestock farming. Additionally, a significant portion of them are unaware of the agreements, initiatives, public policies, and other actions implemented by the GAD to strengthen and support their productive activities. This is compounded by the fact that there is no adequate diagnosis of the economic component, as the community expresses that this parish has not developed economically in recent years. Based on the identified problems, improvement actions are proposed.